Women, identity and activism in Asian and Pacific community economics - Gibson, Katherine (2002)
Katherine Gibson argues that as an antidote to capitalist globalization it is necessary to identify the full range of economic identities that people occupy and the multiple directions that local economic transformation might take. She suggests that an economic politics of place can build upon the disinctiveness of the diverse economies that inhabit specific economic landscapes. Using the lens of a diverse economy, she elaborates what community economy activism might be and introduces three stories of women's role in building and strengthening non-capitalist community economies in place. - Reproduced.
Keywords: Women